Interfacial engineering of oxygenated chemical bath–deposited CdS window layer for highly efficient Sb2Se3 thin-film solar cells. (August 2019) - Guo, L.; Zhang, B.; Li, S.; Montgomery, A.; Li, L.; Xing, G.; Zhang, Q.; Qian, X.; Yan, F.
Abstract: Antimony chalcogenides with quasi-one-dimensional nanoribbon structures represent a new group of cost-effective, non-toxic, and earth-abundant materials for photovoltaics. In this work, interfacial engineering of oxygenated chemical bath–deposited (CBD) CdS buffer layers were used to tailor Sb2 Se3 thin-film solar cells using close space sublimation (CSS) deposition process. Sb2 Se3 solar cells with oxygenated CBD CdS have demonstrated a champion power conversion efficiency of 6.3% with graphite as back contact. Van der Waals (vdW) gap in Sb2 Se3 is regulated via oxygen diffusion, which significantly influences the growth direction of (Sb4 Se6 )n quasi-one-dimensional nanoribbons. The improved interface quality and ribbon orientation, in turn, enhance the electrical and optical properties as well as device performance of the Sb2 Se3 solar cells. The defect level and corresponding device performance associated with the oxygen environment were investigated by both theoretical and experimental approaches. This work provides an effective way to tune the microstructure and electronic structure of non-cubic chalcogenides by tailoring the interfacial area between the window layer and Sb2 Se3 absorber. Graphical abstract: Image 1 Highlights: Oxygenated chemical bath deposited CdS window layer effectively tailors (Sb4 Se6 )n ribbons in Sb2 Se3 solar cells. Photocurrent of Sb2 Se3 was dramatically increased to 28.9 mA cm -2 with oxygenated chemical bath deposited CdS window layer. Power conversion efficiency of 6.3% was achieved with oxygenated CdS as a window layer.